Quality of Family Doctor Contracted Services in Beijing from the Perspective of General Practitioners: A Semi-Structured Interview Study - Cui Yajia; Jin Guanghui (Chinese General Practice Journal)
Background: Home medicine contract service Family doctor contracted service (home medicine service) is an important measure for deepening medical reform in China, aimed at improving people's health level and the efficiency of the health service system. home medicine service Family doctor contracted service has achieved rapid development in terms of quantity, but there is currently a lack of research evidence related to the quality of home medicine service. Objectives: To understand the current status and existing problems of home medicine service family doctor contracted service quality in Beijing from the perspective of general practitioners (GPs), and provide reference for improving the quality of home medicine service family doctor contracted service. Methods: A total of 18 general practitioner GPs from 18 community health service institutions centers in 9 districts of Beijing were selected through purposive sampling from August 2023 to June 2024, and semi-structured interviews were conducted with general practitioner GPs based on the structure process outcome framework interview outline. Analyze tThe data were analyzed through thematic analysis and to extract interview themes. Results: The study extracted 3 themes and 11 sub-themes. Topic 1: The structural quality of home medicine service family doctor contracted service (policy guidance and implementation, institutional conditions and facilities, assessment and incentive mechanisms for home medicine services, home healthcare team building). Topic 2: Process quality of home medicine service family doctor contracted service (contract service content, referral and treatment service process, outpatient service standards). Theme 3: The effectiveness of home medicine service family doctor contracted service (improvement in residents' health levels, increased willingness to seek medical treatment, need to strengthen residents' recognition of home medicine service family doctor contracted service, increased occupational pressure on general practitioner GPs). Conclusions: Since the implementation of home medical service family doctor contracted service, the quality of services has gradually improved, but there are still some limiting factors. We should strengthen policy support, optimize service content and processes, integrate quality evaluation systems with incentive mechanisms, enhance the comprehensive service capabilities of general practitioner GPs and establish efficient home medical familu doctor teams.